When the Textual Critic Assigns Gender: Editing Catullus's Attis Poem. - Weintritt, Jennifer (Helios)
Editors of Catullus 63 face a difficult decision: whether to choose a masculine or feminine pronoun or adjective for Attis after castration at six sites of textual dispute. This article argues that two schools of thought have developed to date: a psychological understanding of Roman gender that analyzes Attis's fluctuating emotions and a somatic one that locates gender identity in the body's (in)ability to change. Neither approach has won a consensus. Combining lessons from the poem's editorial history with premodern trans studies, I offer a different reading of Attis's gender, as entextualized, to provide new insights into interpreting and editing this long-standing textual problem.